Optimised performance of a 23 GHz transciever system for point-to-point microwave link - 295722 Yusnita Rahayu; Jafri Din; Tharek Abdul Rahman, 1955-; International Conference on Communication System (8th : 2002 : Singapore) (Skudai : Universiti Teknologi Malaysia, 2002)
16